Little Person With A Giant Umbilical Cord - Yao, Woo Sze; Wee, Koay Yen (British Journal Of Surgical Science, 2022)
The giant umbilical cord is a rare anomaly that is usually detected in the antenatal period and is distinctive at birth. It is a condition where the diameter of the cord is more than 5 centimeters in diameter. A normal umbilical cord measures approximately 2 centimeters in diameter. We present a case of a giant umbilical cord in a male baby, in whom this condition was diagnosed antenatally. At birth, its appearance is pathognomonic with a large, thickened cord filled with viscid fluid called Wharton’s jelly. The umbilical vessels were apparent from the surface of the cord. Surgical exploration which was done revealed no patent urachus. It is pertinent to rule out other associated anomalies or differential diagnoses when encountering this condition. Keywords : Umbilical anomaly, giant umbilical cord, umbilical pseudocyst